CHIP Premiums, Health Status, and the Insurance Coverage of Children - James Marton; Jeffery C. Talbert (SAGE Publishing, 2010)
This study uses the introduction of premiums into Kentucky's Children's Health Insurance Program (KCHIP) to examine whether the enrollment impact of new premiums varies by child health type. We also examine the extent to which children find alternative coverage after premium nonpayment. Public insurance claims data suggest that those with chronic health conditions are less likely to leave public coverage. We find little evidence of a differential impact of premiums on enrollment among the chronically ill. Our survey of nonpayers shows that 56% of responding families found alternative private or public health coverage for their children after losing CHIP.